The key factor limiting plant growth in cold and humid alpine areas also plays a dominant role in plant carbon isotope discrimination - Xu, Meng; Wang, Guoan; Li, Xiaoliang; Cai, Xiaobu; Li, Xiaolin; Christie, Peter; Zhang, Junling (Frontiers in Plant Science, 2015)
Many environmental factors affect carbon isotope discrimination in plants, yet the predominant factor influencing this process is generally assumed to be the key growth-limiting factor. However, to our knowledge this hypothesis has not been confirmed. We therefore determined the carbon isotope composition (δ13C) of plants growing in two cold and humid mountain regions where temperature is considered to be the key growth-limiting factor. Mean annual temperature (MAT) showed a significant impact on variation in carbon isotope discrimination value (Δ) irrespective of study area or plant functional type (PFT) with either partial correlation or regression analysis, but the correlation between Δ and soil water content (SWC) was usually not significant. In multiple stepwise regression analysis, MAT was either the first or the only variable selected into the prediction model of Δ against MAT and SWC, indicating that the effect of temperature on carbon isotope discrimination was predominant. The results therefore provide evidence that the key growth-limiting factor is also crucial for plant carbon isotope discrimination. Changes in leaf morphology, water viscosity and carboxylation efficiency with temperature may be responsible for the observed positive correlation between Δ and temperature.